Incentives and cooperation in firms: Field evidence - Johannes Berger; Claus Herbertz; Dirk Sliwka (Institute for the Study of Labor (IZA), 2011)
We empirically investigate the impact of incentive scheme structure on the degree of cooperation in firms using a unique and representative data set. Combining employee survey data with detailed firm level information on the relative importance of individual, team, and company performance for compensation, we find a significant positive relation between the intensity of team incentives and several survey measures of cooperation. Moreover, higher powered team incentives are associated with lower degrees of absenteeism while this is not the case for individual incentives.
urn:nbn:de:101:1-201104114052
Keywords: D23; J33; M52; M54; 330; incentives; cooperation; teams; helping effort; Arbeitsgruppe; Leistungsanreiz; Kooperation; Fehlzeit; Schätzung; Deutschland